The developmental activities engaged in by elite youth soccer players who progressed to professional status compared to those who did not - Ford, P. R.; Williams, A. M. (Psychology of Sport and Exercise, 2012)
Objectives We examined differences in the development pathways of elite youth soccer players in England who progressed to professional status in adulthood compared to those who did not. Design Comparative research design. Method Participants were elite youth soccer players (n = 32, 15 years of age). They completed the Participation History Questionnaire (PHQ; Ford, Low, McRobert, & Williams, 2010) under supervision. Results The participation history profiles of professional players followed the early engagement pathway in which they engaged in significantly more soccer play and practice compared to elite youth players who did not become professional, supporting previous work (e.g., Ford, Ward, Hodges, & Williams, 2009). The two groups of players engaged in four other sports, suggesting greater diversification than previously reported for soccer players, but less than that found in studies of team sport athletes in Australia and North America. Conclusions Professional soccer players in England follow an early engagement pathway during childhood and early adolescence.